Predicting functional decline in older emergency patients—the Safe Elderly Emergency Discharge (SEED) project. (8th December 2016) - Lowthian, Judy A.; Straney, Lahn D.; Brand, Caroline A.; Barker, Anna; Smit, P. de Villiers; Newnham, Harvey; Hunter, Peter; Smith, Cathie; Cameron, Peter A.
Abstract: Objective: to profile the trajectory of, and risk factors for, functional decline in older patients in the 30 days following Emergency Department (ED) discharge. Methods: prospective cohort study of community-dwelling patients aged ≥65 years, discharged home from a metropolitan Melbourne ED,  31 July 2012 to 30 November 2013. The primary outcome was functional decline, comprising either increased dependency in personal activities of daily living (ADL) or in skills required for living independently instrumental ADL (IADL), deterioration in cognitive function, nursing home admission or death. Univariate analyses were used to select risk factors and logistic regression models constructed to predict functional decline. Results: at 30 days, 34.4% experienced functional decline; with 16.7% becoming more dependent in personal ADL, 17.5% more dependant in IADL and 18.4% suffering deterioration in cognitive function. Factors independently associated with decline were functional impairment prior to the visit in personal ADL (Odds Ratio [OR] 3.21, 95% confidence interval [CI] 2.26–4.53) or in IADL (OR 6.69, 95% CI 4.31–10.38). The relative odds were less for patients with moderately impaired cognition relative to those with normal cognition (OR 0.38, 95% CI 0.19–0.75). There was a 68% decline in the relative odds of functional decline for those with any impairment in IADL who used an aid for mobility (OR 0.32, 95% CI 0.14–0.7). Conclusion: older people with pre-existing ADL impairment were at high risk of functional decline in the 30 days following ED presentation. This effect was largely mitigated for those who used a mobility aid. Early intervention with functional assessments and appropriate implementation of support services and mobility aids could reduce functional decline after discharge.